Does corporal punishment erode the quality of the mother–child interaction in early childhood?. Issue 3 (28th November 2019) - Laible, Deborah; Davis, Alexandra; Karahuta, Erin; Van Norden, Clare
Abstract: Corporal punishment is believed to exert its influence partially on children's externalizing behavior by undermining the quality of parent‐child relationships, but empirical evidence for this belief is lacking. Thus, the goal of this study was to explore longitudinally whether the use of corporal punishment by mothers was associated with declining quality in parent‐child interactions and whether these declines mediated the links between corporal punishment and later externalizing behavior. Based on data from the NIHCD SECCYD, the findings from this study indicated that the links between the quality of parent‐child interaction and corporal punishment were bidirectional: high quality parent‐child interaction was associated with less use of subsequent corporal punishment by mothers, and maternal use of corporal punishment at 36 months was associated with declines in the quality of parent‐child interaction at 54 months. There were not significant indirect effects of corporal punishment at 36 months on grade 3 aggression through 54 month parent‐child interaction quality, however, which suggests other mechanisms might account for the links between early corporal punishment and later externalizing problems.